TBK1 Mutation Spectrum in an Extended European Patient Cohort with Frontotemporal Dementia and Amyotrophic Lateral Sclerosis. Issue 3 (19th January 2017) - van der Zee, Julie; Gijselinck, Ilse; Van Mossevelde, Sara; Perrone, Federica; Dillen, Lubina; Heeman, Bavo; Bäumer, Veerle; Engelborghs, Sebastiaan; De Bleecker, Jan; Baets, Jonathan; Gelpi, Ellen; Rojas‐García, Ricardo; et al.
Abstract : TANK‐binding kinase 1 (TBK1) mutation spectrum in frontotemporal dementia and amyotrophic lateral sclerosis. Transcript analysis of TBK1 p.Arg127 * nonsense mutation indicating degradation of the mutant cDNA (A). Neuropathology features of FTD‐ALS patient with TBK1 in‐frame deletion mutation p.Thr79del showing abundant TDP‐43 protein aggregates in neurons and oligodendroglial cells (B). Impact of TBK1 in‐frame deletions and missense mutations on NFκB activity in the IFN pathway (C). ABSTRACT: We investigated the mutation spectrum of the TANK‐Binding Kinase 1 ( TBK1 ) gene and its associated phenotypic spectrum by exonic resequencing of TBK1 in a cohort of 2, 538 patients with frontotemporal dementia (FTD), amyotrophic lateral sclerosis (ALS), or FTD plus ALS, ascertained within the European Early‐Onset Dementia Consortium. We assessed pathogenicity of predicted protein‐truncating mutations by measuring loss of RNA expression. Functional effect of in‐frame amino acid deletions and missense mutations was further explored in vivo on protein level and in vitro by an NFκB‐induced luciferase reporter assay and measuring phosphorylated TBK1. The protein‐truncating mutations led to the loss of transcript through nonsense‐mediated mRNA decay. For the in‐frame amino acid deletions, we demonstrated loss of TBK1 or phosphorylated TBK1 protein. An important fraction of the missense mutations compromised NFκB activation indicating that at least some functions of TBK1 are lost. Although missense mutations were also present in controls, over three times more mutations affecting TBK1 functioning were found in the mutation fraction observed in patients only, suggesting high‐risk alleles ( P = 0.03). Total mutation frequency for confirmed TBK1 LoF mutations in the European cohort was 0.7%, with frequencies in the clinical subgroups of 0.4% in FTD, 1.3% in ALS, and 3.6% in FTD‐ALS.